2014
DOI: 10.3892/mmr.2014.2674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of suppressor of cytokine signaling 1 silencing on human melanoma cell proliferation and interferon-γ sensitivity

Abstract: The aim of the current study was to observe the effects of suppressor of cytokine signaling 1 (SOCS1) silencing in human melanoma cells on cell biological behavior and interferon-γ (IFN-γ) sensitivity, and to investigate the use of SOCS1 as a therapeutic target in the treatment of melanoma. Western blot analysis and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) were used to verify that SOCS1 interference effectively silenced the expression of SOCS1 in the Mel526 human melanoma cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In this way, SOCS modulates the ubiquitination of a variety of proteins, which are subsequently recognised by the proteasome and degraded. Parrillas et al (2013) previously reported that SOCS1 is associated with degradation of Cdh1 and blockades melanoma cells in mitosis by G2/M arrest via regulation of cyclin D and cyclin E. G1/S arrest was also reported in melanoma cells treated with a JAK inhibitor and was associated with reduced STAT3 activation ( Xu et al , 2015 ). In the present study, we found that SOCS1 had cell cycle inhibitory activity at the G2/M phase in GC cells.…”
mentioning
confidence: 92%
“…In this way, SOCS modulates the ubiquitination of a variety of proteins, which are subsequently recognised by the proteasome and degraded. Parrillas et al (2013) previously reported that SOCS1 is associated with degradation of Cdh1 and blockades melanoma cells in mitosis by G2/M arrest via regulation of cyclin D and cyclin E. G1/S arrest was also reported in melanoma cells treated with a JAK inhibitor and was associated with reduced STAT3 activation ( Xu et al , 2015 ). In the present study, we found that SOCS1 had cell cycle inhibitory activity at the G2/M phase in GC cells.…”
mentioning
confidence: 92%
“…The study further verified an inverse correlation between miR-221/222 expression and SOCS1 expression serum or in liver tissue in rats. 10 The results of Xu et al 11 The finding herein exhibited that ALT, AST, and ALP were positively correlated with SOCS1 gene expression but the exact mechanism behind this correlation needs further research.…”
Section: Discussionmentioning
confidence: 73%
“…The results of Xu et al proved SOCS1 as a vital target to influence therapeutic effects of melanoma because silencing SOCS1 expression in Mel526 cells reportedly influenced cell cycle, increased cell sensitivity to IFN‐γ, and inhibited the proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of FOXO1 promotes cell proliferation and tumorigenesis, and has thus become a primary target of tumorigenesis prevention (48,49). IRF1 is involved in the regulation of interferon α and β transcription, and it has been demonstrated that IRF1 gene deletion or rearrangement correlates with the development of human cancers (50,51). The glucocorticoid receptor is a member of the nuclear receptor family, which acts as a ligand-dependent transcription factor to regulate gene expression.…”
Section: Discussionmentioning
confidence: 99%